The Role of Technology in Enhancing Students’ Digital Literacy - Salsabila, Unik Hanifah; Maragustam, Maragustam; Murtono, Murtono (Jurnal Pendidikan Progresif, 2024)
The Role of Technology in Enhancing Students' Digital Literacy. Objective: To ascertain the function of technology integration in augmenting digital literacy proficiency and to explore the mediating influence of heutagogy in elucidating the correlation between technology integration and digital literacy. Methods: A quantitative method was utilized to examine data from student responders in the "Islamic Religious Education" curriculum at five campuses in Yogyakarta. Data was gathered using internet surveys. The PLS-SEM model was employed to examine direct and mediated effects, as well as multigroup analysis to investigate any discrepancies in test outcomes. Findings: The inclusion of technology does not immediately influence students' digital literacy. Heutagogy effectively facilitates the impact of technology integration on enhancing digital literacy. The incorporation of technology intended to improve digital literacy among final-year students exhibits a detrimental effect, which can be mitigated through heutagogical intervention. Conclusion: The findings corroborate prior research emphasizing the significance of policy context, culture, and student demographics as determinants affecting the efficacy of technology integration in enhancing digital literacy. Keywords: digital literacy, heutagogy, higher education, learning, islamic religious education, technology integration.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024116